How Do Agricultural Policy Restrictions to Global Trade and Welfare Differ across Commodities? - Lloyd, Peter J.; Croser, Johanna L.; Anderson, Kym (2012)
For decades the world's agricultural markets have been highly distorted by national government policies, but very differently for different commodities. Hence a weighted average across countries of nominal rates of assistance or consumer tax equivalents for a product can be misleading as an indicator of the trade or welfare effects of policies affecting that product's global market. This is especially the case when some countries tax and others subsidize its production or consumption. This article develops a new set of more-satisfactory indicators for that purpose, drawing on the recent literature on trade restrictiveness indexes. It then exploits a global agricultural distortions database recently compiled by the World Bank to generate the first set of estimates of those two indicators for each of 28 key agricultural commodities from 1960 to 2004, based on a sample of 75 countries that together account for more than three-quarters of the world's production of those agricultural commodities. These reveal the considerable extent of reforms in agricultural policies of developing as well as high-income countries over the past two decades.